INTELLECTUAL PROPERTY RIGHTS (IPRs) MANAGEMENT AS A STRATEGY OF CORPORATE ADVANTAGE: CASE STUDY PT CIPTA SARANA KENAYU LESTARI - Septilina Melati Sirait; Achmad Fudholi; Gede Bayu Suparta (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Every company needs a knowledge-based management including knowledge in managing intellectual property in order to make innovation continuously to anticipate dynamic change of environment. The purpose of this research was to assess the management of innovation and intellectual property management to be used as the strategy of corporate advantage on PT Cipta Sarana Kenayu Lestari (PT CSKL). This research was a qualitative study producing the descriptive data in a form of the written or spoken words from the respondents. The respondents were the top management of PT CSKL that were selected by purposive sampling. The method to collect the data were interview, observation, documentation and literature methods. Then the data were systematically analyzed by arranging the data and derive a conclusion. The result showed that PT CSKL has managed many innovations both of product and process. PT CSKL was aware of the importance of innovation and IPR protection into business process by registering to the Director General of Intelectual Property Rights (IPRs). However, from the existing regime, PT CSKL only managed brand and trade secret. This was because of limited cost and facilities classified as PT CSKL is small and medium enterprises. Some intellectual property which were not registered were logo’s company, formula of honey lipstick, website, brochure and packaging design. IPR protected by law is used as a strategy advantage of PT CSKL in doing business development strategy. This strategy starts from the management of innovation in family firms into strategic corporate level towards good corporate governance and cooperation strategic alliance, followed by a strategic business level towards to Porter’s focus strategic and competitive strategic as industrial fragmented and strategic level functional in production, marketing, finance and research and development and quality control.Keywords: innovation, intellectual property rights, strategic advantage, PT Cipta Sarana Kenayu Lestari.